UTILIZATION OF METHYLAMINE COMPOUND AS CO2 ABSORBENTS FOR - Andi Agung Perdana; Maming Maming; Muhammad Zakir (Hasanuddin University, 2015)
Utilization of methylamine as CO2 absorbent to measure carbon-14 activity of coral sample has been done. The objective of this research is to Determine the age of Coral Sample through Activity Measurements of carbon-14 with LSC (Liquid Scintillation Counting) method. Sample were taken from Langkai Island which is far from human activities. Sample preparation includes physical and chemical leaching to produce a clean white sample. Carbon in the sample was released as CO2 by reaction with HCl 10 % and than absorbed by methylamine yield carbamate compound. Absorbed carbon in 1 mL absorber was 0,044 g from the results of weight reduction before and after absorption. The specific activity of the coral sample was 14.56 DPM/g C. Age of the coral sample based on the specific activity was 408.48 ± 43.69 years.